Etnografia de rua: uma reflexão sobre os abrigos de ônibus de Goiânia - Paiva, Rodrigo Balestra Ferreira de (2017)
This dissertation deals with the different ways of designing a shelter for people for loading and unloading, commonly called a bus shelter or Boarding and Unloading Point – PED, through new strategies and design methodologies, and proposes to analyze also the situation of this urban furniture in the context of the city of Goiânia. It proposes guidelines for future projects that can make this object more symbolic, technological and emotional, helping to establish a greater bond with its users and with the city itself. The PEDs must fulfill their primary functions: guide, inform and protect passengers from the elements, and can also become a highlight in the city landscape. Its immediate surroundings require the attention and care of the authorities to offer accessibility, comfort, efficiency and attributes relevant to the user population. When analyzing its insertion in the metropolitan transport system, there are differences between the conception, implantation and maintenance of bus shelters, and the users' needs regarding the positioning of public managers and system operators. The adoption of new assistive technologies can facilitate the life of the user and also promote the valuation of public transportation, mobility and urban accessibility. These are strategies that qualify the experience and create new business opportunities and the production of new Design products.